4. Relasi Bisnis dan Politik: Studi Kasus Gejala Krisis Air Bersih di Badung Selatan, Bali - Anggun Saputri, Kadek Naraiswari; Susiatiningsih, Hermini; Pertiwi, Sheiffi Puspa (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
Massive development of tourism accommodation in South Badung have caused water crisis indication which can threaten human security of local society. Water crisis indication is one of critical issue in environmental security. However, there is no joint effort between host government and hotel chain to overcome this problem. This research is aimed to explain why there is no joint effort between host government and hotel chain. This research uses Neo-Marxism and Human Security. Neo-Marxism explains the dependency of developing countries over developed countries investment through MNCs, including in tourism sector by hotel chain. Furthermore, Human Security is used to explain the effect of tourism development over water crisis indication as a serious threat for local society. The result of this research shows that politics and CSR preference are the causative factors. Although most of hotel chainâ€™s CSR are charity that evoke skepticism, hotel chain should have been held responsible to help host government in overcoming water crisis indication in South Badung.Â